Genetic Mapping of a QTL Controlling Fruit Size in Melon (Cucumis melo L.) - Fazle Amin; Nasar Ali Khan; Sikandar Amanullah; Shusen Liu; Zhao Liu; Zhengfeng Song; Shi Liu; Xuezheng Wang; Xufeng Fang; Feishi Luan (Plants)
Fruit size is an important agronomic trait affecting the yield and commercial value of melon and a key trait selected for during domestication. In this study, two respective melon accessions (large-fruited M202008 and small-fruited M202009) were crossed, and developed biparental mapping populations of the F2 generation (160 and 382 plants) were checked across two subsequent experimental years (2023 and 2024). The phenotypic characterization and genetic inheritance analysis showed that melon fruit size is modulated by quantitative genetics. Bulked segregant sequencing analysis (BSA-seq) identified a stable and effective quantitative trait locus (QTL, named Cmfs) controlling fruit size, localized to a 3.75 Mb region on chromosome 9. To better delineate the main-effect Cmfs locus, co-dominant polymorphic molecular markers were developed in this genetic interval, and genotyping was performed within the F2 mapping populations grown across two years. QTL analysis of the phenotypic and genotypic datasets delimited the major-effect Cmfs locus interval for fruit length [2023: logarithm of odds (LOD) value = 6.16, 16.20% phenotypic variation explained (PVE); 2024: LOD = 5.44, 6.35% PVE] and fruit diameter (2023: LOD value = 5.48, 14.59% PVE; 2024: LOD = 6.22, 7.22% PVE) to 1.88 and 2.20 Mb intervals, respectively. The annotation analysis across the melon genome and comparison of resequencing data from the two parental lines led to the preliminary identification of MELO3C021600.1 (annotated as cytochrome P450 724B1) as a candidate gene related to melon fruit size. These results provide a better understanding for further fine mapping and functional gene analysis related to melon fruit size.